1978
DOI: 10.1128/iai.21.1.114-123.1978
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Infection of Mice with Staphylococcus aureus

Abstract: The survival of Staphylococcus aureus in the lungs of mice was studied under various conditions. Doses of 107 to 109 washed staphylococci were quantitatively introduced into the lungs after intratracheal inoculation in mice under either ether or sodium pentobarbital anesthesia. Mice were sacrificed at intervals, the lungs were excised and homogenized, and the cocci were enumerated by plate count. The 50% lethal dose was 6 x 108 cocci per mouse, and mice died within 24

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…However, while rodent models of chronic infection have been well characterized for Gram-negative pathogens such as Pseudomonas and nontuberculous mycobacteria ( 37 , 38 ), development of a reliable chronic MRSA model has been challenging ( 39 ), in part due to the steep mortality curve associated with the infection. As such, we and others in this field have resorted to using acute pulmonary infection models to establish initial in vivo proof of concept ( 34 , 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, while rodent models of chronic infection have been well characterized for Gram-negative pathogens such as Pseudomonas and nontuberculous mycobacteria ( 37 , 38 ), development of a reliable chronic MRSA model has been challenging ( 39 ), in part due to the steep mortality curve associated with the infection. As such, we and others in this field have resorted to using acute pulmonary infection models to establish initial in vivo proof of concept ( 34 , 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…When the organisms are instilled intratracheally, they are eliminated rapidly by phagocytic ingestion (9,10) and other extracellular killing mechanisms (11,24). For example, DeMaria and Kapral (5) demonstrated that elimination of at least 99% of the inoculum occurs within 48 h in mice inoculated with 10 8 CFU of staphylococci by this method. However, the lack of a satisfactory animal model, in which pathogens remain in the lung in adequate numbers for a sufficient period of time, manifesting clear pathologic features of infection, has been one of the major impediments to the study of the pathogenesis and therapy of staphylococcal pulmonary infection.…”
mentioning
confidence: 99%
“…We and others think that extracellular killing of staphylococci occurs in murine lungs (3,12) and suggest that steroid-induced defects may involve this extracellular killing activity. The mechanism for extracellular killing is unknown but could involve, for example, the production of reactive oxygen species during prostaglandin synthesis (12).…”
Section: Discussionmentioning
confidence: 86%